Penentuan Level Optimum Persediaan Spare Parts di PT. XYZ Menggunakan Minimum Maximum Stock Level (MMSL) - Nurike Oktavia; Rapni Nasution; Wahyuni Amalia (Program Studi Teknik Industri Universitas Setia Budi, 2022)
XYZ company in Sumatera area is operating in the business of oil palm plantation and oleochemicals processing. Its production is based on the supply of mostly from company-owned plantation. In this push system of raw material, production runs continuously resulting the reliability of the machine becomes essential. Material and spare part that support machine cannot be replenish at time when it needed. Thus, overstock can be due to the high cost of storing as well as the risk of storing products. This study aims to calculate minimum and maximum level of inventory that have been the most often stockout occur. The calculation is carried out by Minimum-Maximum Stock Level (MMSL) method on refillable oxygen, turalik oil, steel nut bolt 3/4x3”, steel nut bolt 3/4x4”, welding wire RB 26 dia. 3.2 mm and welding wire LB 52 dia. 3.2mm. MMSL in this study accommodate basic economic order quantity (EOQ). Calculation displays the minimum level, mximum level and optiml order quantity for all six materials. The results are then compared with the actual data and it was found that high fluctuations caused the minimum level results to be in high level and the range between the minimum-maximum levels becomes narrow. One aspect of the reckoning is the demand rate which is calculated by dividing the annual demand by the number of working days. Such justifications should not be used on data with high fluctuations. Therefore, MMSL with basic EOQ should be used on data with small standard deviation Keywords: level minimum, level maximum, safety stock, economic order quantity